2014
DOI: 10.1111/1469-0691.12619
|View full text |Cite
|
Sign up to set email alerts
|

The Clostridium difficile PCR ribotype 027 lineage: a pathogen on the move

Abstract: Clostridium difficile is a Gram-positive, spore-forming, human and animal pathogen that is the major cause of antibiotic-associated diarrhoea worldwide. The past decade has seen the rapid emergence of the hypervirulent PCR ribotype (RT) 027 complex, which has been associated with increases in the incidence and severity of disease and mortality. In this review, we describe the potential virulence factors that have been reported in strains from the RT 027 complex. We review the emergence, population structure, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 88 publications
(118 reference statements)
0
73
1
2
Order By: Relevance
“…C. difficile ribotype 027 is one of the most serious outbreak-associated C. difficile strains responsible for multiple outbreaks in North America, Europe, and beyond (7,53). It produces both toxin A and toxin B and an additional toxin, the CDT binary toxin (12).…”
Section: Discussionmentioning
confidence: 99%
“…C. difficile ribotype 027 is one of the most serious outbreak-associated C. difficile strains responsible for multiple outbreaks in North America, Europe, and beyond (7,53). It produces both toxin A and toxin B and an additional toxin, the CDT binary toxin (12).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, specific focus was placed on two ribotypes, 027 and 014-020. For years, ribotype 027 has been studied as a hypervirulent and/or epidemic ribotype and has often been found to be responsible for greater numbers of CDI than other ribotypes [27, 28]. Interestingly, while multiple studies have found greater levels of toxin for isolates of ribotype 027 [17, 21, 29], this phenotype has not been consistently correlated to disease severity in humans in all studies [15, 17].…”
Section: 0 Discussionmentioning
confidence: 99%
“…The increase in CDI severity has been coincident with the spread of hypervirulent strains such as restriction endonuclease analysis type BI, which is also known as North American pulsedfield electrophoresis type 1 (NAP1) or ribotype 027 [6e9]. In addition to toxin A (TcdA) and toxin B (TcdB), PCR ribotype 027 strains have also been found to produce a binary toxin (CDT) [10].…”
Section: Introductionmentioning
confidence: 99%